Cost-minimization analysis comparing subcutaneous trastuzumab at home with intravenous trastuzumab for HER2-positive breast cancer in Singapore - Yanting Ouyang; Han Yi Lee; Fun Loon Leong; Han Jieh Tey; Vivianne Shih; Elaine Hsuen Lim; Nicholas Graves (Therapeutic Advances in Medical Oncology)
Background: Trastuzumab (Herceptin) can be administered intravenously (IV Herceptin) and subcutaneously, with similar efficacy and safety, but with differences in dosage and costs. Previous studies have evaluated the costs of both treatment approaches in the outpatient settings, but no study has compared the costs of IV Herceptin administered in outpatients with subcutaneous Herceptin administered at patients’ homes (Homecare SC Herceptin). Objectives: This study aimed to compare the per-patient costs of Homecare SC Herceptin versus IV Herceptin administered in a healthcare institution’s outpatient setting in Singapore. Designs: We performed a model-based cost-minimization analysis to estimate and compare the per-patient annual costs associated with each treatment modality from a societal perspective. Methods: Direct cost comprised healthcare resources utilization: drug, consumables, manpower, facility and cardiac assessment. Indirect cost was valued using a human capital approach to account for productivity lost by patients. Monte Carlo simulations with 1000 iterations were performed to account for parameter uncertainties. Costs were reported in 2023 Singapore dollars. Results: The annual societal cost per patient receiving IV Herceptin ranged from S$64,194 to S$65,135, while for Homecare SC Herceptin, it ranged from S$25,865 to S$26,807. Homecare SC Herceptin reduced the annual cost burden by 58.8% and 59.7%, per non-metastatic and metastatic breast cancer patient, respectively. The primary cost contributor was drug therapy, comprising more than 90% of the total cost. Even when excluding the cost of drugs, Homecare SC Herceptin remained cheaper by S$1912 annually. The cost reduction is approximately 60% compared to IV Herceptin regardless of disease status, with a 100% probability that the decision to adopt Homecare SC Herceptin leads to cost savings in Singapore. Conclusion: Treatment of breast cancer with Homecare SC Herceptin is a cost-saving option compared to IV Herceptin.